Hospitality graduates’ career intentions during COVID-19: evidence from Malaysia - Ng, Kok Ann*; Trupp, Alexander *; Phongpanichanan, Charuwan* (Taylor and Francis Group, 2022)
In the context of COVID-19 and a transforming industry, it is important to evaluate future hospitality graduates’ commitment and motivation towards work and employment. This research thus asks, how do future hospitality graduates make career decisions during the COVID-19 pandemic? The theoretical framework draws on Positive Psychological Capital (PsyCap) and Social Cognitive Career Theory (SCCT), whilst the empirical data derives from semi-structured interviews and informal conversations with hospitality graduates in Malaysia. Findings concerning the career decision-making process highlight the role of family on career intention, as well as the surprisingly positive career outlook during COVID-19, and show that work exposure reinforces and influences intention to stay in the industry.